2019
DOI: 10.18261/issn.1891-943x-2018-04-05
|View full text |Cite
|
Sign up to set email alerts
|

Information Skills of Finnish Basic and SecondaryEducation Students: The Role of Age, Gender, Education Level, Self-efficacyand Technology Usage

Abstract: The information skills and technology use of 3,159 Finnish 12-22-year-old students were examined in this study. Data were collected using the combination of a usage habit questionnaire and a performancebased test that measured their skills when choosing a medium to seek information, defining search queries, and selecting and evaluating search results. On average, these students' information skills were found to be insufficient. Particularly, students failed in creating search phrases, and they tended to concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
1
8
0
2
Order By: Relevance
“…According to the ICILS (International Computer and Information Literacy Study) 2013 and 2018, ICT self-efficacy is positively related to computer and information literacy among 8th-grade students (Fraillon et al , 2019; Hatlevik et al , 2018). However, in Kaarakainen et al ’s (2018) study, self-efficacy was found to have a positive effect only on male students’ information skills.…”
Section: Literature Reviewmentioning
confidence: 55%
See 2 more Smart Citations
“…According to the ICILS (International Computer and Information Literacy Study) 2013 and 2018, ICT self-efficacy is positively related to computer and information literacy among 8th-grade students (Fraillon et al , 2019; Hatlevik et al , 2018). However, in Kaarakainen et al ’s (2018) study, self-efficacy was found to have a positive effect only on male students’ information skills.…”
Section: Literature Reviewmentioning
confidence: 55%
“…Primary and secondary school students have been exposed to digital media throughout their lives. Their Web-related skills develop along with their age and education levels (van Deursen and van Diepen, 2013; Kaarakainen et al , 2018). However, there are remarkable differences in skill levels among students (Hatlevik and Christophersen, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…I en granskning av ämnena matematik och teknik från den svenska Skolinspektionen ansågs användningen av digitala resurser i undervisningen vara låg (Skolinspektionen, 2019). Tidigare studier har pekat på brister i finländska elevers kompetens i informationssökning, och problemet är synligt även generellt i ICILS-rapporten (ICILS, 2019;Kaarakainen et al, 2018;OECD, 2015). Lärare har överlag en positiv inställning till användning av digitala resurser i undervisningen (Fraillon et al, 2019), men mer fortbildning anses behövas.…”
Section: Digitaliserad Skola -Förändrad Undervisning?unclassified
“…Blikstad-Balas, 2012och Paakkari, 2020. Speglar vi detta mot vetskapen om stora brister i elevers sökstrategier (ICILS, 2019;Kaarakainen et al, 2018) kan vi konstatera att förutsättningarna och villkoren för innehållsligt lärande blir olika för olika elever.…”
Section: Digitaliserad Skola -Förändrad Undervisning?unclassified